2010
DOI: 10.1186/1477-7827-8-14
|View full text |Cite
|
Sign up to set email alerts
|

Short term hypothyroidism affects ovarian function in the cycling rat

Abstract: BackgroundRats made hypothyroid with propilthyouracil start showing abnormal cycling on the second cycle after the start of the treatment, with a high proportion of spontaneous pseudopregnancies and reduced fertility.MethodsTo investigate some of the mechanisms involved in these reproductive abnormalities, hypothyroidism was induced in virgin rats by propilthyouracil (0.1 g/L in the drinking water) and we determined circulating hormones by radioimmunoassay and whole ovary expression of ovarian hormone receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 46 publications
6
32
2
1
Order By: Relevance
“…GH stimulates IGF-1 secretion in the liver and in the mammary stroma, therefore a paracrine role of GH modulating the effects of other hormones on proliferation and differentiation of mammary epithelium must not be ruled out (28). The present results demonstrated that hypothyroidism diminishes the secretion of GH in the rat, supporting previous studies (29).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…GH stimulates IGF-1 secretion in the liver and in the mammary stroma, therefore a paracrine role of GH modulating the effects of other hormones on proliferation and differentiation of mammary epithelium must not be ruled out (28). The present results demonstrated that hypothyroidism diminishes the secretion of GH in the rat, supporting previous studies (29).…”
Section: Discussionsupporting
confidence: 82%
“…It has been previously shown that hypothyroidism can increase serum levels of PRL during estrous without changing basal secretion on diestrous day (29). In the present study, based on the similar values of circulating PRL between the treatments, we cannot attribute a relevant role of this hormone on mammary carcinogenesis.…”
Section: Discussioncontrasting
confidence: 41%
“…For example, lower Igf-I levels are found in rodents that are hypothyroid and in females that do not go through proestrus (70), and both chronic HPA axis activation and circadian disruption are associated with obesity (71,72). We did note a marked overlap between the endocrine profile of Magel2-null mice and that of rodents with congenital leptin resistance, in contrast to rodents with diet-induced obesity.…”
Section: Endocrine Phenotypes Of Magel2-null Mice Resemble Those Founmentioning
confidence: 73%
“…The presence of these receptors in the uterus could be related to the implantation process. Hyper or hypothyroidism affect the implantation sites, the incidence of resorptions (7)(8), the oxidative status in the uterus (9), and the leucocyte infiltration into the endometrial stroma (4) in rats. Additionally, hypothyroidism reduces the weight of the uterus in rats (40) as well as the number and force of the uterine contractions in bitches (11) and rats (5)(6).…”
Section: Discussionmentioning
confidence: 99%
“…Both hyperthyroidism and hypothyroidism have been associated with menstrual disturbances, miscarriages, and infertility in women (1)(2). Hyper or hypothyroid rats show modifications in the angiogenesis and proliferation of luteal cells of the corpus luteum (3), the amount of carbohydrates in the ovaries and endometrium (4), the oviductal and uterine contractility (5)(6), the implantation sites and the incidence of resorptions (7)(8), and the oxidative status of the uterus (9). Hypothyroidism increases the size of oviductal epithelial cells in rabbits (10).…”
Section: Introductionmentioning
confidence: 99%